Motorcycle evolution, design, passion - Walker, Mick (Johns Hopkins Universtiy Press, 2006)
In a survey that ranges from the late nineteenth-century pioneers like Gottlieb Daimler and Hildebrand & Wolfmuller to present-day manufacturers-Harley Davidson, Ducati, Honda, BMW, Aprilia, and Triumph-Walker sets each model within its historical context and outlines the main technological and stylistic innovations that make each bike unique.